STUDI AWAL POTENSI HYDROPOWER SEBAGAI SOLUSI KEBUTUHAN ENERGI LISTRIK BAGI MASYARAKAT PINGGIRAN KOTA PALEMBANG - Pramadhony Pramadhony; M . Lazim; Ozkar F. Homzah; Rachmat D Sampurno; Heriyanto Rusmaryadi (Jurnal Turbulen, 2019)
Electrical energy is needed by the citizen of Indonesia including in Palembang City. Palembang is growth rapidly, in contrast there is still citizen who has not enjoyed  the electricity especially who is living in Sukamulya Village, Sematang Borang Sub-ditrict. Constructing a Micro Hydro Powerplant is an effort to facilitate an electircity to the area which has not been covered by PT. PLN. Howefer before constructing a hydro  power plant, a study should be conducted in order to estimate the potency of electrical power which could be generated. Therefore the authors have collected some primary datas such as dimension of river, velocity of water and geographical condition. These datas is used to calculate the potency of energy, either in form of potential or kinetic energy. Based on the on-site observation, all locations have no enough elevation difference. Nevertheles the onlyform of  energy which can be converted into electrical energy is kinetic energy, which determined by the river flow velocity. The fastest river flow is found  in Location of B amounting 0.35 m/s. By optimazing the dimension of turbine and considering the efficiency of transmision and generator, it predicts Turbine, located in Location B, can generate electrical energy with the maximum power of 66.26 Watt. Based on the results, the electrical power potency in all locations are low and did not fullfill the requirements. The power can be increased by levelling up the elevation of the upstream. It can be done by constructing a dam which  integrated with irrigation system. Nevertheles it need a future study in order to predict the impacts. Keywords: : Micro Hydro Powerplant, Energy Potency,  River Flow,  Palembang city